Development of a Reference Book on the Charm of Macroscopic Fungi in Lubuklinggau Based on Exploration of the Surrounding Nature to Strengthen SDG-Oriented Learning - Reny Dwi Riastuti; Mareta Widiya (Postgraduate, University of Mataram, 2025)
The teaching of plant taxonomy in Indonesia still faces limitations in the availability of teaching materials that are relevant to local conditions, requiring the development of contextual learning resources that are appropriate to local potential and meaningful. This study addresses the scarcity of specialized, locally relevant teaching materials for the Lower Plant Taxonomy course. We developed a reference book,